Science, technology, and innovation in pandemic times: Covid-19 implications - Vargas, Marco Antonio; Alves, Nathalia Guimarães; Mrejen, Matias (Cadernos do Desenvolvimento, 2023)
The paper analyzes the impacts of the COVID-19 pandemic on the organization of and incentive to science, technology, and innovation in health activities worldwide and nationally, focusing on two aspects. One of them is related to the adopted mechanisms of coordination of and support to these activities in order to manage the pandemic. The other is related to the recent evolution of scientific production on Covid-19. This study highlights the strategic importance of public research and incentive institutions in organizing and coordinating science, technology, and innovation in health activities and the growing incorporation of new technological platforms associated with Industry 4.0. However, there are worldwide asymmetries in the production of scientific knowledge. So, a strategic State approach is crucial in order to coordinate public and private interests regarding health production and guarantee the population’s access to health.